The Phospholipase D2 Knock Out Mouse Has Ectopic Purkinje Cells and Suffers from Early Adult-Onset Anosmia. - Matthieu M Vermeren; Qifeng Zhang; Elizabeth Smethurst; Anne Segonds-Pichon; Heinrich Schrewe; Michael J O Wakelam (PLoS ONE)
Phospholipase D2 (PLD2) is an enzyme that produces phosphatidic acid (PA), a lipid messenger molecule involved in a number of cellular events including, through its membrane curvature properties, endocytosis. The PLD2 knock out (PLD2KO) mouse has been previously reported to be protected from insult in a model of Alzheimer's disease. We have further analysed a PLD2KO mouse using mass spectrophotometry of its lipids and found significant differences in PA species throughout its brain. We have examined the expression pattern of PLD2 which allowed us to define which region of the brain to analyse for defect, notably PLD2 was not detected in glial-rich regions. The expression pattern lead us to specifically examine the mitral cells of olfactory bulbs, the Cornus Amonis (CA) regions of the hippocampus and the Purkinje cells of the cerebellum. We find that the change to longer PA species correlates with subtle architectural defect in the cerebellum, exemplified by ectopic Purkinje cells and an adult-onset deficit of olfaction. These observations draw parallels to defects in the reelin heterozygote as well as the effect of high fat diet on olfaction.